EFFECTIVE STOMATOLOGICAL MAINTENANCE OF PEDIATRIC PATIENT WITH LESCH–NYHAN SYNDROME - N. V. Tarasova; V. G. Galonskii (Вопросы современной педиатрии, 2014)
A rare clinical case of stomatological maintenance of 11-year old boy with Lesch-Nyhan syndrome (primary x-linked hyperuricemia) is demonstrated in the article. In order to decrease trauma risk of oral cavity organs and soft tissues (due to autoagression) individual dentoalveolar occlusive mouthguards for the upper and lower jaws were used.  As a result of this procedure pain syndrome was arrested, the child became quieter and the possibility to provide him with individual education according to the specialized correction school program appeared. Usage of such palliative measures in severe clinical cases is a method of choice in the absence of positive effect of alternative methods of treatment.